Hiding Techniques using Mp3 - Shyma Mohammed; Ahmed Nori (Al-Rafidain Journal of Computer Sciences and Mathematics)
In last years, Steganography techniques involving audio file formats appear to be increasing in popularity. This may be attributed to the fact that current steganalysis tools available to the general public fall short when applied to audio files. Another factor that may be contributing to the increasing popularity is the widespread popularity of the MP3 file format and its ubiquitous presence on the Internet. In this paper, an introductory look at steganography and the important methods for hiding data in audio is shown, as well as the strengths and weaknesses of each method. An overview about sound and their file formats especially MP3 file format and its attribute and features. Here, some steganography techniques on sound (Low Bit Encoding, Phase Coding) has been used to apply them on MP3 file format which had been chosen as a cover for data transmission.